A PSYCHOLOGICAL ANALYSIS OF HEDONISM IN JAMES CAMERON’S MOVIE “TITANIC” - Nurmadina, Nurmadina; Sulaiman, Iskandar; Burhamzah, Muftihaturrahmah (Journal of English Literature and Linguistic Studies, 2025)
This research analyzes the types of hedonism present in James Cameron's movie Titanic using Weijer's (2012) theory and applies Freud's (2010) psychoanalytic approach to examine these hedonistic behaviors. Additionally, the research assesses the effects of hedonism based on Veenhoven's (2003) theory. The findings reveal 26 instances of hedonistic behavior, with psychological hedonism being the most prevalent among the four identified types: psychological hedonism, ethical hedonism, hedonistic egoism, and hedonistic utilitarianism. Through the psychoanalytic lens, the id is identified as the dominant structure driving these behaviors. Furthermore, the study indicates that the characters in the film predominantly experience positive effects from their hedonistic actions.